Efeito anti-inflamatório de formulações para aplicação tópica de ácido oleico e acetato de dexametasona em modelos experimentais de inflamação de pele - Pegoraro, Natháli Schopf (2021)
The skin, as an interface space between the environment and the body, is constantly exposed to harmful effects from the external environment, which are capable of evoking an inflammatory response. Since the treatment for skin inflammation has limitations due to the severity of the adverse effects caused, there is a constant need in the world scenario regarding the development of therapeutic alternatives to treat these affections. In this study, we developed formulations for the topical application of oleic acid (OA), a compound known to modulate mechanisms adjacent to wound healing. The first chapter of this thesis addresses the development of formulations based on Lanette® and Pemulen® TR2 containing OA and the evaluation of the anti-inflammatory effect of these formulations in a skin burn model in Swiss mice. Both formulations containing 3% OA inhibited the ultraviolet B (UVB) radiation-induced ear edema after single treatment (Imax = 79.36 ± 7.47% and 92.58 ± 2.58%, respectively). Pemulen® TR2 3% OA reduced inflammatory cell infiltration (Imax = 46.7 ± 4.0%) and ear edema after repeated treatment (Imax = 69.88 ± 2.31%; 60.95 ± 5.70% e 29.89 ± 6.40% at 24 h, 48 h and 72 h after UVB). In the second chapter, we verified that Pemulen® TR2 3% OA was able to inhibit the ear edema (Imax = 76.41 ± 5.69%), the infiltration of inflammatory cells (assessed by myeloperoxidase enzyme activity) (Imax = 71.37 ± 10.97%) and the level of the inflammatory cytokine interleukin (IL)-1β (Imax = 94.18 ± 12.03%) induced by croton oil in mice. Pemulen® TR2 3% OA inhibited ear edema in a model of persistent inflammation caused by successive croton oil administrations (Imax = 85.75 ± 3.08%), as well as inhibiting IL-1β-induced ear edema (Imax = 80.58 ± 2.45%). In both experimental models, we observed that the antiedematogenic effect is due, at least in part, to the action of OA on glucocorticoid receptors, since this effect was prevented by the glucocorticoid receptor antagonist mifepristone. This anti-inflammatory effect of Pemulen® TR2 3% OA was not associated with the occurrence of adverse effects usually caused by the use of glucocorticoids. These results suggest that the semisolids developed could be promising alternatives to treat inflammatory skin lesions. An alternative to improve treatment efficacy and limit the occurrence of adverse effects is the use of Nanotechnology. In this sense, a perspective for the conclusion of this study is. the association of OA and dexamethasone into nanostructured systems, benefiting from their advantages for the delivery of the active molecules, in order to propose a potential therapy to treat cutaneous inflammatory disorders.